Reduced attention toward faces, intentionality and blame ascription in violent offenders and community‐based adults: Evidence from an eye‐tracking study. Issue 2 (17th January 2022) - Zajenkowska, Anna Maria; Bodecka, Marta; Duda, Ewa; Lawrence, Claire
Abstract: People typically have a strong bias in attention toward faces to help them understand social interactions. Nonetheless some people, like incarcerated offenders and psychopaths, exhibit deficits in "face reading, " which may impair their interpretations, especially in case of attribution allocation in harmful events. In these cases, the ascription of intentionality is key in understanding the allocation of blame and structuring social information processing. Consequently, in the current study, in addition to typically studied intentionality and blame ascription levels (subfactors of hostile attributions), we also propose a new indicator of hostile attributions: intentionality/blame isomorphism, indicating reduced differentiation between those two factors. Violent prison inmates ( N = 63) and community‐based adults without previous history of incarceration ( N = 63) took part in an eye‐tracking study. In line with our hypotheses, offenders exhibited reduced attention orienting to faces as well as greater intentionality/blame isomorphism. In the case of both groups, people looked longer at the faces of the harm doer compared with the harm receiver. Additionally, greater intentionality/blame isomorphism predicted reduced attention to faces; however, when group status was included in the model, it became the only significant predictor of the attention to faces. Future studies should examine the origins of these gaze and attribution patterns and investigate consequences related to social perception and interactions of people prone to violence.